Neuroeducation and teaching perception: a systematic review from the qualitative approach - Belén Valdés-Villalobos; Mariana Lazzaro-Salazar (Institute of Advanced Engineering and Science, 2026)
Neuroeducation is a discipline that considers aspects contributed by the natural sciences, including cognitive abilities, brain functioning, and the emotional system, among others, as topics derived from knowledge in fields such as neuroscience, cognitive science and psychology, and which are articulated in the social domain. The aim of the present review was to learn about teachers’ perceptions of neuroeducation and to determine which qualitative methods are most commonly used in this field of research. The review followed the guidelines of the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method, searching the databases with the highest impact between 2015-2023. The selection process yielded nine eligible studies and they were analyzed in terms of the type of knowledge studied and the methods used in neuroeducational research. The results discuss the most frequently developed qualitative methodologies in the neuroeducational discipline, offering recommendations from the methodological cluster to strengthen future research in the discipline. Therefore, this study promotes neuroeducational research from a qualitative approach will improve the resonance between neuroeducation experts and teachers. Furthermore, it highlights the importance of proposing situated research, using descriptive methodologies in the field, which communicate in a language appropriate to educators and their context.